ZIRCON REACTION AND STABILITY OF THE U-PB ISOTOPE SYSTEM DURING INTERACTION WITH CARBONATE FLUID: EXPERIMENTAL HYDROTHERMAL STUDY - Rizvanova N.G.; Levchenkov O.A.; Maslenikov A.V.; Komarov A.N.; Makeev A.F.; Levskiy L.K.; Belous A.E.; Bezmen N.I. (My University, 2000)
The interpretation of metamorphically induced U-Pb isotopic discordance requires a thorough understanding of zircon-fluid interactions. With this aim we have studied the behaviour of metamict and crystalline zircon phases and their U-Pb systems by cathodoluminescence after treatment by 2M Na2CO3 solution at T = 200–800 °C and P = 1–5 kbar for 3–14 days, X-ray diffraction, microprobe and isotope dilution analysis. The data indicate that zircon transformation under hydrothermal conditions depends on the experimental conditions and the degree of structural damage. Reconstitution of defective and impurity-enriched zones of metamict zircon (homogenization of impure element concentrations and increase of crystallinity) was observed at 400 °C and P = 1 kbar. Considerable lead and uranium loss occurred under these conditions. As a result of zircon dissolution, newly formed baddeleyite accommodating U from 2M Na2CO3 solution and Zr-Na-silicate were recognized. This process intensified with increasing pressure. Study of crystalline zircon indicates that migration of U and Pb took place only during dissolution of zircon at T above 650 °C. In the presence of carbonate-ions essential U and Pb amounts are lost from metamict zircon at a lower P-T than is typical for greenschist facies metamorphism.